Hasil Belajar IPA Kelas V Dengan Model Pembelajaran Examples Dan Non Examples Berbantuan Power Point - Isnarahayu Mawaddah; Harjono, Ahmad; Istiningsih, Siti (Educational Consultant & Counseling Career (EC3) Mataram, 2022)
This study aims to determine the effect of the examples non examples learning model assisted by power point media on the science learning outcomes of class V students. The population in this study is class V SDN 3 Darek. In this research design, the research design used was a quasi-experimental research design, a non-equivalent control group design type. The data collection technique used the test method for science learning outcomes which had previously been tested for validity, reliability, level of difficulty, and differentiating power. testing requirements analysis using normality test and homogeneity test. The data analysis technique used t-test with polled variance t-test with a significance level of = 5%. the results of the polled variant t test, obtained tcount = -5,092 < ttable = 2,048 so it can be said that H0 is accepted and Ha rejected, this shows that there is no effect of the examples non examples learning model of power point media on the science learning outcomes of fifth grade students at SDN 3 Darek year the 2021-2022 school. Keywords: Examples and Non Examples learning model, Power Point, Science Learning Outcomes